Adipose Tissue An Update - Szablewski, Leszek (Physiology, 2019)
Adipose tissue, a kind of connective tissue, plays different and significant roles in the human body. Its function includes protection against environmental factors, storage of lipids and triacylglycerol, and the process of thermogenesis. It is also involved in the secretion of highly active biomolecules such as steroid hormones, prostaglandins, as well as proteins called "adipokines." On the other hand, disturbances in functions of adipose tissue may cause several pathologies such as obesity and insulin resistance. Obesity is a worldwide health problem, whereas diabetes mellitus due to insulin resistance is defined by the World Health Organization as "a progressive worldwide epidemic." Especially dangerous is visceral accumulation of adipose tissue.This book describes a series of up-to-date topics about physiological and pathological processes in adipose tissue.